1959
DOI: 10.1063/1.1730051
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Unreacted Hugoniot for Liquid TNT

Abstract: An optical technique was used to measure the state behind high-explosive induced shock waves in un-e~~ted liquid TNT. Da~a are reported which determine the unreacted Hugoniot for this material, at an Imtlal temperature of 81 C, over the pressure range from 45 kilobars to 110 kilobars. 200 150 P KB 100 50 \ \ \ \ \ \

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1961
1961
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…11, 16 Garn also previously performed shock compression experiments on molten TNT with an initial density of q 0 ¼ 1.472 g/cm 3 between 353.7-355.3 K up to 11 GPa (110 kilobars), above which higher stress shock input conditions resulted in apparent detonation. 17 Garn 17 did not comment on observable degradation of the TNT just above melt, and his explosively-driven experiments indicated that molten TNT is less sensitive than pressed or cast TNT. The von Neumann spike condition, P VN ¼ 26.5 GPa, for molten TNT (using a steady detonation velocity of D s ¼ 6.63 km/s, and the initial molten density) however, was found to be similar to that estimated by Sheffield et al, Kury et al, and others 18 for pressed or cast TNT, P VN ¼ 25 GPa (q 0 ¼ 1.624 g/cm 3 , D s ¼ 6.85 km/s).…”
mentioning
confidence: 99%
“…11, 16 Garn also previously performed shock compression experiments on molten TNT with an initial density of q 0 ¼ 1.472 g/cm 3 between 353.7-355.3 K up to 11 GPa (110 kilobars), above which higher stress shock input conditions resulted in apparent detonation. 17 Garn 17 did not comment on observable degradation of the TNT just above melt, and his explosively-driven experiments indicated that molten TNT is less sensitive than pressed or cast TNT. The von Neumann spike condition, P VN ¼ 26.5 GPa, for molten TNT (using a steady detonation velocity of D s ¼ 6.63 km/s, and the initial molten density) however, was found to be similar to that estimated by Sheffield et al, Kury et al, and others 18 for pressed or cast TNT, P VN ¼ 25 GPa (q 0 ¼ 1.624 g/cm 3 , D s ¼ 6.85 km/s).…”
mentioning
confidence: 99%
“…Its widespread use has been unparalleled, stemming from attractive properties that include chemical stability, low cost, relative insensitivity, and ease of melt casting. TNT, however, reacts rapidly under shock conditions at pressures exceeding 11 GPa, 4 and little is known about its highpressure phase diagram or chemical reactions leading to initiation and detonation. The experimental observation of molecular dimerization by dynamic time-of-flight mass spectrometry has pointed to the possibility of Diels-Alder chemistry above ϳ12 GPa in anthracene and toluene under shocked conditions, and more recently in TNT at similar pressures.…”
mentioning
confidence: 99%
“…3 with respective Rankine-Hugoniot analyses. 4,[14][15][16][17][18][19][20][21] Most materials display linear shock velocityparticle velocity ͑U s -u p ͒ behavior in the absence of phase transitions. 22 While this relation is strictly empirical, it is consistent with a first-order expansion of the Mie-Grüneisen equation.…”
mentioning
confidence: 99%
“…For NM IV , ρ 0 and α 0 are calculated with the fit ρ 0 (kg/m 3 ) = 1152.0 − 1.1395 × T 0 (C) − 1.665 × 10 −3 × T 2 0 (C) in Berman and West [50]. For IPN, the data are those in [46], for NPNA3, those in Bernard, Brossard, Claude and Manson [51] and, for TNT, those in [47] and [52], except for c 0 , identified to the constant a of the linear asymptote D = a + bu to Garn's shock Hugoniot measurements [53]. The derivatives of D (exp) CJ necessary to implement the IM (Subsect.3.4) could be found only for NM and IPN.…”
mentioning
confidence: 89%